Genomic insights into the adaptation of Synechococcus to the coastal environment on Xiamen - Zhang, Ting; Zhou, Kun; Wang, Yanhui; Xu, Jinxin; Zheng, Qiang; Luo, Tingwei; Jiao, Nianzhi (Frontiers in Microbiology, 2023)
Synechococcus are widely distributed in the global ocean, from the pelagic zone to coastal waters. However, little is known about Synechococcus in coastal seawater due to limitations in isolation and culture conditions. In this study, a combination of metagenomic sequencing technology, flow cytometry sorting, and multiple displacement amplification was used to investigate Synechococcus in the coastal seawater of Xiamen Island. The results revealed 18 clades of Synechococcus and diverse metabolic genes that appear to contribute to their adaptation to the coastal environment.Intriguingly, some metabolic genes related to the metabolism of carbohydrates, energy, nucleotides, and amino acids were found in 89 prophage regions that were detected in 16,258 Synechococcus sequences. The detected metabolic genes can enable prophages to contribute to the adaptation of Synechococcus hosts to the coastal marine environment. The detection of prophages also suggests that the cyanophages have infected Synechococcus. On the other hand, the identification of 773 genes associated with antiviral defense systems indicates that Synechococcus in Xiamen have evolved genetic traits in response to cyanophage infection. Studying the community diversity and functional genes of Synechococcus provides insights into their role in environmental adaptation and marine ecosystems.